2010
DOI: 10.1021/jp9119827
|View full text |Cite
|
Sign up to set email alerts
|

DFT Studies of Solvation Effects on the Nanosize Bare, Thiolated, and Redox Active Ligated Au55 Cluster

Abstract: The structural and electronic properties of the bare Au 55 cluster, and of the model thiol passivated Au 55 (SCH 3 ) 42 , the redox active ligated Au 55 S(CH 2 ) 2 CO 2 (CH 2 ) 10 bpy • 2Cl and Au 55 (SCH 3 ) 41 (S(CH 2 ) 2 CO 2 (CH 2 ) 10 bpy) • 2Cl (bpy ) N-methyl-4,4′-bipyridinium) complexes are studied at the DFT level in the gas phase and with an explicit water layer. For all complexes, neutral, positive, and negative charge states are investigated. The thiol ligation distorts the outer layer of the appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 75 publications
2
7
1
Order By: Relevance
“…Also, as it is known that the chemical reactivity of a molecule is dependent on the H-L gap in an inverse manner, if the gap is larger, lower would be the reactivity. 42 As is well known, chemically reactive systems would transfer charges more, and we find that our results on charge-transfer also reflect the same -the higher the H-L gap, the stronger would be the chemical reactivity leading to the larger chargetransfer. In fact, it can be qualitatively seen by comparing the columns 3/4 and 5 of Table 2.…”
Section: Electronic Propertiessupporting
confidence: 78%
See 1 more Smart Citation
“…Also, as it is known that the chemical reactivity of a molecule is dependent on the H-L gap in an inverse manner, if the gap is larger, lower would be the reactivity. 42 As is well known, chemically reactive systems would transfer charges more, and we find that our results on charge-transfer also reflect the same -the higher the H-L gap, the stronger would be the chemical reactivity leading to the larger chargetransfer. In fact, it can be qualitatively seen by comparing the columns 3/4 and 5 of Table 2.…”
Section: Electronic Propertiessupporting
confidence: 78%
“…Finally, it is known that the chemical reactivity of a molecule is dependent on the H-L gap in an inverse manner-that is, higher the gap, lower the reactivity. 41 Assuming that the charge-transfer will occur only when a system is chemically reactive, we find that our results on charge-transfer also reflects the same -larger the H-L gap, greater the chargetransfer (please compare columns 2/3 and 4 of table 3) -though, not quantitatively. find that the spin-polarized H-L gap of TCNQ-GQD complex has an origin in the spinpolarized charge-transfer from GQD to TCNQ.…”
Section: Electronic Propertiesmentioning
confidence: 67%
“…Parameter FEFFIT H [12] FEFFIT QH [12] Since in this particular case EXAFS spectrum alone does not contain sufficient information, one can use the findings from other methods to distinguish between the two possible geometries. In particular, as was mentioned before, both DFT simulations [12] and our modelling using Sutton-Chen potential suggest that icosahedral geometry is more likely for Au147 (and smaller [59]) gold nanoparticles. Therefore, to conclude our discussion on the structure of Au147 nanoparticles, in Table 4 we list the values of structure parameters, obtained from our RMC/EA simulations for Au147 nanoparticles with icosahedral ge-ometry.…”
Section: Structure Of Gold Nanoparticlessupporting
confidence: 76%
“…In our previous study, we speculated that 32 thiolates are bound to the facet of the Au 55 core having an icosahedral or cuboctahedral motif, similar to the case of Au 55 (PR 3 ) 12 Cl 6 , which has a cuboctahedral Au 55 core . A recent computational study performed at the density functional theory (DFT) level on Au 55 (SCH 3 ) 32 revealed that this cluster has a local minimum structure in which a deformed icosahedral Au 55 core is coordinated with 32 RS ligands via Au−SR single bonds . However, with the Au core−RS shell structure model, we cannot explain why Au 54 (SC 18 H 37 ) 30 and Au 55 (SC 18 H 37 ) 31 prefer the Au 54 core and 31 thiolate ligands, respectively.…”
Section: Resultsmentioning
confidence: 89%